Dynamic capabilities facilitate the use of technology to promote organizational ambidexterity - Yunita, Tyna; Sasmoko, Sasmoko; Bandur, Agustinus; Alamsjah, Firdaus (Business: Theory and Practice, 2024)
The organizational ambidexterity of commercial banks has been the subject of recent research. As a novelty, research has yet to be conducted on the banking sector in a dynamic environment. This study’s goal is to identify the variables that affect ambidextrous banking. The research methodology uses quantitative techniques with six constructs: organizational ambidexterity (OA), dynamic capability (D-CA), organizational culture (O-CU), human capital (H-CA), and technological capacity (T-CA) with moderator environmental dynamism (E-DY). The research questionnaire was measured using seven Likert scales, and the data was processed using structural equation modeling and Smart PLS software. The results of all hypothesis tests are as follows: First, technological capacity, organization culture, and dynamic capability have a positive effect on organizational ambidexterity. Second, technological capacity, human capital, and organizational culture have positive results for a positive effect on dynamic capability. Third, the moderating effect of E-DY on the relationship between T-CA and OA has a negative and significant impact. Fourth, the moderating effect of E-DY on the relationship between O-CU and OA is insignificant. Fifth, the moderating influence of E-DY on the link between dynamic capability and organizational ambidexterity has a positive and significant impact. This study will contribute to the theoretical aspect by enriching the theory that human resource management, technological capacity, organizational culture, and dynamic capabilities are essential in organizational ambidexterity.